1989
DOI: 10.1007/bf00262034
|View full text |Cite
|
Sign up to set email alerts
|

Study on pathogenesis of Enterococcus faecalis in urinary tract

Abstract: The rate of isolation of Enterococcus faecalis as the causative bacterium of complicated urinary tract infections has been increasing. However, the pathogenicity of this bacterium in the urinary tract has not been clarified. Thus, the authors investigated how E. faecalis is pathogenic to the urinary tract, using mice with experimental urinary tract infection. The investigation revealed that this bacterium when sufficiently numerous can be directly pathogenic. The bacterium can be pathogenic indirectly when pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The ability of E. faecalis to cause pyelonephritis in an experimental mouse model of infection has been reported elsewhere (8). In these experiments, E. faecalis alone when used to infect the bladders of mice at a concentration of 10 8 CFU caused pyelonephritis in 50% of infected animals after 7 days.…”
Section: Discussionmentioning
confidence: 77%
“…The ability of E. faecalis to cause pyelonephritis in an experimental mouse model of infection has been reported elsewhere (8). In these experiments, E. faecalis alone when used to infect the bladders of mice at a concentration of 10 8 CFU caused pyelonephritis in 50% of infected animals after 7 days.…”
Section: Discussionmentioning
confidence: 77%
“…However, the lack of a robust animal model of enterococcal UTI has impeded the study of this pathogen within the urinary tract. In previously established models of ascending UTIs, E. faecalis fails to establish persistent bladder colonization and primarily displays tropism to the kidneys (21,29,43,56,61,75). The absence of persistent infections in these murine models reflects the profile of E. faecalis in community-acquired UTIs where this bacterium represents less than 5% of clinical isolates (55).…”
Section: E Faecalis Establishes Persistent Infections In the Bladdersmentioning
confidence: 99%
“…Several rodent models have been developed to study E. faecalis pathogenesis in the urinary tract in single and mixed infections with other Gram-negative pathogens (21,29,43,61,75). These models involve the transurethral inoculation of bacterial suspensions into the bladders of healthy animals or streptozocin-induced diabetic animals (56) and have been shown to be primarily useful for the study of E. faecalis-mediated pyelonephritis.…”
mentioning
confidence: 99%
“…The present studies focused on lipoteichoic acids, cell wall components of gram-positive bacteria, for the following reasons: (1) gram-positive bacteria (e.g., enterococci) are recognized as pathogens in UTI (Hirose et al, 1989;Wells et al, 1990); (2) attachment to epithelial cells, including epithelial cells in the urinary tract, enhances the ability of lipoteichoic acids (LTs) produced by these bacteria to trigger mucosal inflammation (Beachey and Courtney, 1989); (3) under experimental conditions, LTs migrate to areas considerably remote from their site of injection (Leon and Panos, 1987) and accumulate in tissues where they are likely to induce pathogenesis (Hyzy et al, 1992); and (4) repeated administration of LT in vivo has been shown to cause gross morphological changes in the basement membrane of the urothelium and cells in the basal layer of the urothelium (Leon and Panos, 1987).…”
mentioning
confidence: 99%